Determination of pesticide residues in coconut water by liquid-liquid extraction and gas chromatography with electron-capture plus thermionic specific detection and solid-phase extraction and high-performance liquid chromatography with ultraviolet detection - Brito, N. M.; Navickiene, S.; Polese, L.; Jardim, EFG; Abakerli, R. B.; Ribeiro, M. L. (Elsevier B.V., 2002)
Two simple methods were developed to determine, 11 pesticides in coconut water, a natural isotonic drink rich in salts, sugars and vitamins consumed by the people and athletes. The first procedure involves solid-phase extraction using Sep-Pak Vac C-18 disposable cartridges with methanol for elution. Isocratic analysis was carried out by means of high-performance liquid chromatography with ultraviolet detection at 254 nm to analyse captan, chlorothalonil, carbendazim, lufenuron and diafenthiuron. The other procedure is based on liquid-liquid extraction with hexane-dichloromethane (1:1, v/v), followed by gas chromatographic analysis with effluent splitting to electron-capture detection for determination of endosulfan, captan, tetradifon and trichlorfon and thermionic specific detection for determination of malathion, parathion-methyl and monocrotophos. The methods were validated with fortified samples at different concentration levels (0.01-12.0 mg/kg). Average recoveries ranged from 75 to 104% with relative standard deviations between 1.4 and 11.5%. Each recovery analysis was repeated at least five times. Limits of detection ranged from 0.002 to 2.0 mg/kg. The analytical procedures were applied to 15 samples and no detectable amounts of the pesticides were found in any samples under the conditions described. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: beverages; food analysis; coconut water; pesticides; organochlorine compounds; organophosphorus compounds; benzimidazole; benzophenylurea; thiourea compounds